Orientasi Politik Kelas Milenial Dalam Pemilihan Gubernur : Sebuah Catatan Survey - Muhammad Tanzil Aziz Rahimallah; Aenal Fuad Adam; Faturachman Alputra Sudirman (EKONOMI & SOSIAL, 2019)
This study aims to explain the behavior of millennial class voters in elections in local politics in Indonesia. The millennial class is seen as a rational and critical voter, in fact the variable of similarity in social identity, regionalism becomes a determining factor in the political preference of the millennial class. This study uses a survey method with a total of 400 respondents. This article confirms that the sociological approach and regional, language and ethnicity similarity variables are determinants in influencing the political preferences of millennial classes in explaining the phenomenon of voter behavior in the context of local politics in Indonesia.